Association of Histone Methyltransferase G9a and Overall Survival After Liver Resection of Patients With Hepatocellular Carcinoma With a Median Observation of 40 Months. Issue 2 (January 2016) - Bai, Kai; Cao, Yi; Huang, Chao; Chen, Jianwei; Zhang, Xiaojin; Jiang, Yi
Abstract : Abstract: Approximately 50% of patients with hepatocellular carcinoma (HCC) reside in China. HCC is associated with very high mortality compared with other cancers. Although numerous factors influence the survival of patients with HCC who undergo liver resection, the role of the tumor biomarker histone methyltransferase (G9a) is unknown. We enrolled 350 patients with HCC who underwent liver resection and followed them for 40 months. Patients' clinicopathologic characteristics were acquired from medical records, and overall survival was determined using multiple methods. We conducted an immunohistochemical analysis of study G9a expression in HCC tissues. We used χ 2 test to evaluate the significance of the relationships between G9a and other factors and Cox proportional hazards regression to estimate the hazard ratios and 95% confidence intervals. The levels of alpha-fetoprotein were significantly higher in patients with G9a-positive tumors. TNM stage, elevated alpha-fetoprotein level, and G9a overexpression were associated with worse outcomes. High expression of G9a was associated with worse outcomes, indicating that G9a may serve as a prognostic biomarker for patients with HCC who undergo surgical resection. Because of its role in cell proliferation, G9a represents a potential therapeutic target.